Efeitos do treinamento físico aeróbio na resposta pulmonar em modelo experimental de DPCO: envolvimento da STAT3 - Rangel, Maysa Alves Rodrigues Brandão (2016)
The chronic obstructive pulmonary disease (COPD) is a preventable and treatable pulmonary disease, characterized by the presence of chronic air flux obstruction, which is not totally reversible. The air flux obstruction is commonly progressive and is associated to an abnormal inflammatory lung’s response, caused mainly by smoking. The cytokines play the main role is this inflammatory response, and are coordinated by lots of cellular and molecular pathways, including the Janus quinase (JAK) and the signal transductor and activator of transcription (STAT) paths. The aerobic physical training (APT), taken correctly, provides anti-inflammatory effects to the airways experimental models of COPD. However, no research has analyzed any possible cellular and molecular pathways related to APT effects on COPD until the present moment. This present study analyzed the APT’s effects of light intensity on an ergometric treadmill (5x/a week, 30 days, 1h/a session), in an experimental COPD model, in C57Bl/6 male mices. The COPD model used cigarettes` smoke exposition 2 times a day, for 90 days. After the 60 first days of exposition to cigarettes` smoke, the COPD + APT experimental group started the APT for 30 days. In this way, the experimental groups were: Control (n = 20), APT (n = 20), COPD (n = 20) and COPD + APT (n = 20). The experimental model could induce pulmonary emphysema, which was analyzed through the comparison of the alveolar medium diameter (p<0.001) with the Control group, which alteration was completely inhibited by APT (p<0.001). Beyond the emphysema, the experimental model also induced chronic bronchitis, observed through the gathering of total cells (p<0.001), of neutrophils (p<0.001), of lymphocytes (p<0.001) and of macrophages (p<0.001) in the bronchoalveolar lavage fluid (BAL), when compared with the Control group. On the other hand, the APT could inhibit the inflammatory process, diminishing the gathering of total cells (p<0.001), of neutrophils (p<0.001), of lymphocytes (p<0.001) and of macrophages (p<0.001) in the BAL. As a complementary analysis, the pulmonary inflammation was also studied through the histomorphometric technique, where the number of neutrophils, of lymphocytes and of macrophages in the airways’ wall were counted. The COPD experimental model also induced the gathering of neutrophils (p<0.001), of lymphocytes (p<0.001) and of macrophages (p<0.001) in the airways wall, which were all completely inhibited by the APT, including neutrophils (p<0.001), lymphocytes (p<0.001) and macrophages (p<0.001). The COPD model also induced the gathering of collagen fibers (p<0.001) in the airways, which was reduced by the APT (p<0.001). The COPD experimental model also induced increasing levels of IL-1beta (p<0.001), IL-6 (p<0.001), CXCL-1 (p<0.001) and TNF-alfa (p<0.001), compared with the Control group, which were all reduced by APT, including IL-1beta (p<0.001), IL-6 (p<0.001), CXCL-1 (p<0.001) and TNF-alfa (p<0.001), when compared with the COPD group. The COPD model also increased phosphorylated STAT3 expression by peribronchial leukocytes (p<0.001), by leukocytes in the parenchyma (p<0.001) and by bronchial epithelium (p<0.001), compared with the Control group. STAT3 levels were reduced by APT in peribronchial leukocytes (p<0.001), in leukocytes in the parenchyma (p<0.001) and in bronchial epithelium (p<0.001), compared with the Control group. In this way, we concluded that APT of light intensity can reverse the main characteristics of COPD in experimental models and those characteristics apparently are related to STAT3.